Analisis Komparatif Kinerja Keuangan Perusahaan Perbankan Sebelum dan Sesudah Implementasi Teknologi Blockchain - Ramadhani Anhar Fahrezi; Rida Perwita Sari (ARBITRASE: Journal of Economics and Accounting, 2026)
Digital transformation has encouraged the banking industry to adopt various technological innovations to enhance efficiency and competitiveness. One of the most prominent technologies is blockchain, which offers greater transparency, security, and efficiency in financial transaction processes. This study aims to analyze the differences in the financial performance of PT Bank Negara Indonesia (Persero) Tbk before and after the implementation of blockchain technology. A quantitative approach with a comparative research design was employed using the paired sample t-test. The study utilized annual financial statement data of PT Bank Negara Indonesia (Persero) Tbk covering the period from 2015 to 2024. Financial performance was measured using four indicators: Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO). The findings indicate that blockchain implementation has a significant effect on NIM, while no statistically significant differences were found in ROA, ROE, and BOPO. These results suggest that the benefits of blockchain in the banking sector are more evident in enhancing the bank’s intermediation function, as reflected by changes in Net Interest Margin, rather than in improving overall profitability and operational efficiency. This study provides empirical evidence that blockchain implementation does not immediately improve all financial performance indicators but initially affects the bank’s intermediation function, as reflected in changes in Net Interest Margin. These findings contribute to the growing body of literature on blockchain implementation in the Indonesian banking industry and provide valuable insights for future research and managerial decision-making regarding digital transformation in the financial sector.